Respuesta :

Answer:

-30

Step-by-step explanation:

-3ab        original equation

-3(-2)(-5) .          plug in numerical values

6(-5) .             -3 times -2 is 6

-30 .         6 times -5 is -30.

Answer:

-30

Step-by-step explanation:

Plug in -2 for a & -5 for b in the expression given:

-3ab = (-3)(-2)(-5)

Multiply across. Note that:

Negative number x negative number = positive number.

Positive number x negative number = negative number.

(-3)(-2)(-5) = (6)(-5) = -30

-30 is your answer.

~

ACCESS MORE